ANALYSIS OF THE DEGREE OF SATURATION AND LEVEL OF SERVICE ON AHMAD YANI ROAD, EAST SUMBA DISTRICT - Amrita Winaya; Frienly Daungu (Journal Innovation of Civil Engineering (JICE), 2023)
Congestion on Jalan Ahmad Yani in West Sumba Regency is due to the presence of various shopping centers, companies, and tourist attractions. This study aims to determine the degree of saturation and level of service and provide alternative solutions to overcome the level of traffic congestion. The degree of saturation of Jalan Ahmad Yani in directions 1 and 2 is very high because the DS value is more than 1.00. The highest degree of saturation is 1.41 for direction 1 on Friday at 16.00-17.00, while direction 2 is 1369 on Monday at 12.00-13.00. The amount of road capacity is 1,075.41 pcu/hour while the peak flow is 1472 pcu/hour and is included in the level of road service F. Alternative solutions to overcome the level of traffic congestion are widening the road from 5 m to 9 m so that the degree of saturation is only 0.613 and is included in the level of service C. The second solution is directing pedestrians to use the sidewalk but at peak times it is included in the level of service F; conditions are still the same as before removing obstacles, namely traffic flow jams, low speeds, long queues, and delays. Keywords: Congestion; Level of Service; Road Capacity.